Analisis Sistem Pengendalian Intern Atas Pembayaran Gaji Pada PT. AIOLA INDONESIA - Kintan Amelia Kuntjoro (Lembaga Pengembangan Kinerja Dosen, 2024)
The objective of this study is to assess the internal control system utilized in the employee payroll process at PT. AIOLA INDONESIA, examine the procedures employed throughout the employee payroll process, and identify any vulnerabilities in the implemented procedures. This study employs qualitative methodologies to gather data through the means of observations, interviews, and documentation. The findings of this study indicate that the internal control system implemented for the payroll process has successfully met the requirements for segregating functional tasks, authorizing transactions, promoting healthy habits, and ensuring the employment of high-quality personnel. Employees and management can effectively implement the internal control system.